Genome-Wide Association Mapping for Tomato Volatiles Positively Contributing to Tomato Flavor - Zhang, Jing; Zhao, Jiantao; Xu, Yao; Liang, Jing; Chang, Peipei; Yan, Fei; Li, Mingjun; Liang, Yan; Zou, Zhirong (Frontiers in Plant Science, 2015)
Tomato volatiles, mainly derived from essential nutrients and health-promoting precursors, affect tomato flavor. Taste volatiles present a major challenge for flavor improvement and quality breeding. In this study, we performed genome-wide association studies (GWAS) to investigate potential chromosome regions associated with the tomato flavor volatiles. We observed significant variation (1200x) among the selected 28 most important volatiles in tomato based on their concentration and odor threshold importance across our sampled accessions. Using 174 tomato accessions, GWAS identified 125 significant associations (P<0.005) among 182 SSR markers and 28 volatiles (27 volatiles with at least one significant association). Several significant associations were co-localized in previously identified quantitative trait loci (QTL). This result provides new potential candidate loci affecting the metabolism of several volatiles.